Improved staffing policies and practices in healthcare based on a conceptual model - Wei, Ning; Wang, Zhongwei; Li, Xiyuan; Zhang, Yibing; Zhang, Jing; Huang, Ziying; Wang, Xiao (Frontiers in Public Health, 2024)
Background Staffing policies are critical in healthcare facilities. However, problems from a mismatch between staff numbers requirements and offers are frequently encountered. This research examines the joint effects of quantitative and qualitative staff mismatch in a healthcare organization in China to understand how staffing management policies affect staffing adequacy and how staffing adequacy leads to important human resource (HR) outcomes. Methods In a previous study, we identified four dimensions of staffing management policies, namely decision-making, data management, productivity optimization, and title vs. competency. Based on this categorization, an 11-item scale was generated and evaluated for psychometric quality. A quantitative study was conducted with 1,323 healthcare professionals (including clinical and administrative staff) working at the hospital, matched by dyads and teams. A conceptual model with work engagement as a mediator between quantitative staffing adequacy interactions and qualitative staffing adequacy was tested with structural equations. Results The findings indicate that staffing policies do exert effects on staffing adequacy. These findings further indicate that quantitative and qualitative staffing adequacy interact in explaining work engagement and team performance and that the moderated mediation occurs as hypothesized. Conclusion Our findings indicate that both types of staffing adequacies contribute to higher team performance via a heightened sense of work engagement from healthcare professionals. Furthermore, a modulation is observed between the two types of staffing adequacies during the promotion of higher team performance. The supported model is helpful in improving staffing management policies and increasing staffing fit so as to improve hospital performance.